VERSIFIKASI DAN NILAI AKHLAK DALAM DIWAN IBNU ADIM: KAJIAN ILMU ARUDH - Shafira Nandya Setiawan (Yayasan Haiah Nusratul Islam, 2025)
This study aims to analyze the versification (ʿaruḍh) and moral values contained in Diwan Ibn al-ʿAdim. The focus of this research includes identifying the types of baḥr (metrical patterns) and zihaf (metrical variations) used in the composition of the poems, as well as revealing the ethical messages embedded within them. This research employs a descriptive qualitative method, integrating the principles of ʿilm al-ʿarudh in analyzing the metrical structure of the poems and the Islamic ethical approach in interpreting their moral content. The data consist of selected poetic verses from Diwan Ibn al-ʿAdim, obtained from the Diwan al-ʿArabi digital application. The data were analyzed through three stages: (1) classification of the poetic verses, (2) analysis of the wazan, tafʿilah, and baḥr based on the theory of ʿaruḍh, and (3) interpretation of the moral values reflected in the text. The results show that Diwan Ibn al-ʿAdhim predominantly employs Baḥr Basit, Bahr Ṭawil, and Bahr Kamil, with variations of zihaf such as khaban, qabd, and idmar. In terms of moral content, the poems express various Islamic ethical values, including humility (tawaḍu), patience (sabr), honesty (sidq), chastity (iffah), piety (taqwa), cautiousness (wara), wisdom (hikmah), asceticism (zuhd), generosity (karam), and responsibility. Additionally, the work contains ethical teachings that reflect the relationship between humans and Allah SWT, fellow human beings, and the social environment. The study concludes that Diwan Ibn al-Adim is a literary work that excels not only in aesthetic value through its structured metrical system but also in its rich and timeless moral messages. This research contributes to the development of Arabic literary studies, particularly those that integrate formal analysis and ethical interpretation.